Analisis Peran Sistem Informasi Pemerintah Daerah (SIPD) Penatausahaan terhadap Media Pelaporan Keuangan di Badan Perencanaan Pembangunan Daerah Provinsi Jawa Barat - Meynaldi, Reza; Rosalina, Resmi Ranti (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research was conducted to find out the Role of Regional Government Information Systems (SIPD) Administration to Media for Financial Reporting in the Regional Development Planning Board of West Java Province. The method applied in this research is descriptive qualitative with data analysis that has been collected on the independent variable, namely the Regional Government Information System (SIPD) and administration as well as dependent variables, namely financial reporting media. The results of the study show that SIPD has an important role in accessing local government development information. So that efforts that can be made to overcome this are coordination made to the West Java BPKAD as the manager of Regional Financial Information regarding SIPD.